Analisis Strategi Pemasaran Gerilya terhadap Keputusan Pembelian dengan Perceived Value sebagai Variabel Intervening (Studi Kasus pada Konsumen Yakult di Kota Sukabumi) - Mochamad Raditya Hakim; Asep Muhamad Ramdan; Tetty Sufianty Zafar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses the increasing competition in Indonesia’s health beverage industry, which has contributed to declining sales performance despite strong brand recognition. The research aims to analyze the effect of guerrilla marketing strategies on purchasing decisions, with perceived value acting as an intervening variable, among Yakult consumers in Sukabumi City. A quantitative causal-associative approach was employed using survey data collected from 132 respondents selected through purposive sampling. Data were gathered via a structured questionnaire using a semantic differential scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3.2.9. The findings reveal that guerrilla marketing strategies have a positive and significant direct effect on purchasing decisions. Perceived value also shows a significant positive influence on purchasing decisions. Furthermore, perceived value partially mediates the relationship between guerrilla marketing strategies and purchasing decisions, indicating that the effectiveness of guerrilla marketing is strengthened when consumers perceive higher functional, emotional, and social value from the product. These results suggest that personalized and relationship-based marketing approaches are effective in enhancing consumer purchasing decisions, particularly when supported by strong perceived value. The study provides managerial insights for companies in strengthening direct selling strategies to remain competitive in dynamic markets.